The effect of dry cow antibiotic with and without an internal teat sealant on udder health during the first 100 d of lactation : a field study with matched pairs - Mütze, Katja; Wolter, Wilfried; Failing, Klaus; Kloppert, Bärbel; Bernhardt, Heinz; Zschöck, Michael; Justus Liebig University Giessen (My University, 2012)
The objective of this field study was to compare the udder health status as well as the clinical mastitis rate during the first 100 d of lactation in cows that received long-acting dry cow antibiotic alone (group AB) or in combination with an internal teat sealant (group AB + OS). The study was conducted during a 9-month period and included 136 Holstein cows from 12 dairy farms in Hessia, Germany. Between days 1 and 5 after calving a California mastitis test (CMT) was performed. Milk-samples were collected for bacteriological culture before drying off, between days 6 and 14 and days 35 and 56 of lactation. Additionally the cows were monitored for the occurrence of clinical mastitis events until 100 d post partum. Within the 12 herds cow-pairs were formed on the basis of age, milk yield and SCC. A cow-pair consisted of one cow from group AB and one cow from group AB + OS. For statistical analysis within every cow-pair one quarter that has been dried off with internal teat sealant and dry cow antibiotic (group AB + OS) was compared with one quarter that has been dried off with dry cow antibiotic (group AB) alone. As criterion for the matching process of udder quarters the cytobacteriological udder health status before drying off was used. A total of 544 quarters (136 cows) were used in this analysis. In the first 5 d after calving, group AB had significantly more quarters with a positive CMT reaction than group AB + OS (85 vs. 57; P <0·001), and in the first 100 d of lactation, group AB had more quarters with clinical mastitis than group AB + OS (25 vs. 15; P = 0·03). In the time periods 6 14 and 35 56 d of lactation, there were fewer quarters in group AB + OS populated with Corynebacterium spp. (days 6 14, P = 0·05; days 35 56, P = 0·02) and aesculin-positive streptococci (days 35 56, P = 0·02). The internal teat sealant was a promising tool for the prevention of new intramammary infections (IMI) of dry cows with environmental udder pathogens as expressed during early lactation.
Keywords: ddc:630